Determination on the Dissolution Rate of Doxepin Hydrochloride Tablets Produced by Different Manufacturers in China with Fiber-Optic Medicine Dissolution/Release Rate Process Test System - Liao, Yijing; Liu, Xiaoqing; Liu, Chao; Zhou, Gang; Wang, Wei; Mai, Xi; Zhong, Haijun; Tu, Guogang; Huang, Huiming; Wang, Bin (Asian Journal of Chemistry, 2013)
The fiber-optic medicine dissolution/release rate process test system was adopted to investigate the in vitro dissolution rate curves of doxepin hydrochloride tablets on sale produced by nine different pharmaceutical factories in China. Furthermore, we compared the difference of the internal quality of these products and analyzed the controllability of quality of the existing dissolution rate method which provided effective method for drugs’ quality control and the basis for establishment of dissolution rate method and standard. The paddle method was adopted, with a determination wavelength of 292 nm, temperature 37 ºC, rotating speed of 50 r min-1 and the time of detection was 90 min. In different dissolution mediums, the 5 mm fiber-optic probe was adopted to measure the dissolution rate curves of doxepin hydrochloride tablets. Although most of the products of the nine pharmaceutical factories were found to be in accord with the regulation of Chinese Pharmacopoeia 2010. There was great difference in these dissolution curves, indicating that there were great differences in the technological level among the nine pharmaceutical factories. The analytical method used was continuous and convenient and could be used to evaluate the difference of dissolution of solid preparation.